Analysis of the Supervision of Siwa Class III Port Operator Unit Office Employees in an Effort to Realize Passenger Safety and Security at the Siwa Sea Port - Risma Niswaty; Ayu Amini Saputri; Sitti Hardiyanti Arhas (Pinisi Journal of Education and Management, 2022)
This study aims to determine the supervisory performance of the Siwa Class III port management unit office employees in Realizing the Safety and Security of Passengers at the Siwa Sea Port. This study uses qualitative research methods with 5 (five) people, namely the leadership, office employees and ship crew. This research was conducted at the Siwa Class III Port Operator Unit Office. Data collection techniques by means of observation, interviews, and documentation. The data obtained from the research results are processed using data analysis techniques, namely data collection, data reduction, data presentation, conclusion/verification. The results of the study indicate that the analysis of the supervision of the port management unit class III office employees in realizing the safety and security of passengers proves that the performance of employee supervision still needs to be improved, seen from the indicators, namely the supervision procedure is not stable, the supervision standard is not good and the supervision accuracy is quite good